2014
DOI: 10.1177/0022219414529336
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Children With Nonverbal Learning Disabilities, Reading Disabilities, or Typical Development

Abstract: The main goal of the present study was to shed further light on the psychological characteristics of children with different learning disability profiles aged between 8 and 11 years, attending from third to sixth grade. Specifically, children with nonverbal learning disabilities (NLD), reading disabilities (RD), or a typical development (TD) were tested. In all, 15 children with NLD, 15 with RD, and 15 with TD were administered self-report questionnaires to assess different types of anxiety and depression symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 72 publications
(92 reference statements)
3
67
0
6
Order By: Relevance
“…The highest score in the CDI questionnaire indicates higher frequency of complaints related to depression symptoms. Therefore, the results of our sudy demonstrate that children with poor school performance have a larger number of predictive depression signals, consistent with other studies in the literature [21][22][23][24][25] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The highest score in the CDI questionnaire indicates higher frequency of complaints related to depression symptoms. Therefore, the results of our sudy demonstrate that children with poor school performance have a larger number of predictive depression signals, consistent with other studies in the literature [21][22][23][24][25] .…”
Section: Discussionsupporting
confidence: 92%
“…A study 24 that aimed to investigate different profiles of children with learning problems (nonverbal learning disorder, reading disorder) and with a typical development, ages 8 up to 11, showed that children with reading disorders had worse depression symptoms than those with non-verbal learning disabilities and typical development.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several studies found that adults with RD are more anxious than skilled readers (Heiman & Precel, 2003;Mammarella et al, 2014;Nelson & Harwood, 2011) whereas some findings indicate no differences between adults with RD and their non-RD peers (e.g. Thus, several studies found that adults with RD are more anxious than skilled readers (Heiman & Precel, 2003;Mammarella et al, 2014;Nelson & Harwood, 2011) whereas some findings indicate no differences between adults with RD and their non-RD peers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, some recent studies also show higher levels of depression in students with learning disabilities in reading [8,9]. Studies that have focused on analyzing the symptoms of anxiety in students with learning disabilities show similar results.…”
Section: Emotional and Motivational Problems In Spanish-speaking Adolmentioning
confidence: 57%
“…Thus, a different meta-analysis [10] concludes, with a moderate effect size, that 70% of students with reading disabilities have more anxiety problems. Likewise, recent studies report higher anxiety problems in students with reading disabilities [8,9]. However, it is controversial whether internalizing disorders remain present in adolescence and adulthood or whether they decrease with age.…”
Section: Emotional and Motivational Problems In Spanish-speaking Adolmentioning
confidence: 99%